Effect of Project-Based Learning through blogging on EFL students’ writing ability - Ikrima Halimatus Sa'diyah; Bambang Yudi Cahyono (Journal on English as a Foreign Language, 2019)
This study scrutinized how Project-Based Learning (PjBL) through blogging affects the writing ability of EFL students across self-efficacy levels. A quasi-experimental design was applied and it was conducted in nine sessions. It involved forty-one students of the English Department of a state university in East Java, Indonesia who attended the argumentative writing class. PjBL through blogging was conducted on the experimental group, while the conventional method was conducted on the control group. The data were collected from writing tests and self-efficacy questionnaires. Independent sample t-test was used in analyzing the students’ scores. The finding disclosed that the students utilizing PjBL through blogging got better scores in writing than the ones using the conventional method. It was also revealed that students having high self-efficacy and those having low self-efficacy taught using PjBL through blogging had no significant difference in writing ability.